The Effect of Adding Carrot Flour (Daucus carota) to Commercial Feed on Increasing the Brightness of the Body Color of Goldfish (Carassius auratus) - Darsiani Darsiani; Arini Febrianti; Antoni Harahap; Muhammad Ansar; Dewi Yuniati; Dian Lestari; Fauziah Nur; Chairul Rusyd Mahfud; Yanti Mutalib (Airlangga University, 2025)
One type of freshwater ornamental fish that is popular and in demand is the goldfish (Carassius auratus) because it has an attractive color that appears on its body, so food is needed that can trigger the appearance of attractive fish colors. The purpose of this study was to determine the effect of giving carrot flour and the right dose to increase the brightness of the color and growth of goldfish. The research design used was a completely randomized design (CRD) with an experimental method, four treatments, and three replications. The treatments tested were 0% carrot flour + 100% commercial feed (A), 5% carrot flour + 95% commercial feed (B), 10% carrot flour + 90% commercial feed (C), and 15% carrot flour + 85% commercial feed (D). The parameters observed were an increase in color brightness, absolute weight gain, feed conversion ratio, survival rate, and water quality (temperature, DO, and pH). The addition of carrot flour can improve the color brightness of goldfish but has no significant effect on absolute weight growth, feed conversion ratio, or goldfish survival. Water quality parameters measured during the study were still within a reasonable range for goldfish rearing.